Effects of amorphous nano-silica on hydration products of tricalcium silicate at 80 °C - Yuan, Bin; Yang, Shuo; Xu, Bihua; Qiao, Xuan; Duan, Jinzhong (Construction & building materials, 2023)
•The hydration products of pure C3S and nano-SiO2 at 80℃ were studied.•The optimum amount of silicon material at 80℃ differs from that at high temperature.•Decalcification will decrease the Ca/Si of hydration products.•Hight Ca/Si products can be converted into low Ca/Si products by nano-SiO2. The hydration products of G-grade oil well cement can affect its overall performance, which is currently enhanced by nano-silica (nano-SiO2). However, the hydration process and products of silica nanoparticles and cement have not yet been fully clarified. This study focused on tricalcium silicate (C3S), the main component of oil well cement, and analyzed the effects of nano-SiO2 on the hydration products of C3S using 1H low-field NMR, XRD, SEM-EDS, TGA, FTIR, and 29Si MAS NMR at 80 °C. The results showed that after seven days of maintenance and the addition of more than 34% nano-SiO2, due to the agglomeration and adsorption of nano-SiO2, the content of CSH decreases obviously. The added nano-SiO2 reacted with both the volcanic ash of CH and the high Ca/Si products from C3S hydration, resulting in the formation of a large amount of low Ca/Si hydration products and a denser microstructure of the specimen. In addition, the decalcification reaction of nano-SiO2 facilitated the polymerization of CSH and increased the chain length, but the agglomeration of nano-SiO2 and decalcification shrinkage increased the porosity of the specimens.